Prevalence and Correlates of Cervico-Vaginal Clinical Syndromes Among Women Attending a Health Camp in Lalitpur District of Nepal - Johnson, D; Chamot, E; Lhaki, P; Broker, TR; Steben, M; Shrestha, S (Kathmandu University Medical Journal, 2015)
Background Sexual and reproductive health of women is a major public health problem in Nepal. Screening of cervico-vaginal clinical syndromes could potentially provide insights to the prevalence of sexually transmitted infections (STIs), which is not known. Objective To investigate the prevalence and factors associated with cervico-vaginal clinical syndromes in the socio-behavioral, medical, and public health context of Nepal. Methods Married women attending a clinical health camp held by the Nepal Fertility Care Centerin Khokana of Lalitpur district were recruited to the study. Seventy-three participants completed face-to-face questionnaires on basic socio-demographic, behavioral and reproductive health factors and underwent pelvic screening including clinical diagnosis of cervicitis and vaginitis. An univariate analysis was performed to determine if any of the self-reported variables were associated with abnormal pelvic examination (cervicitis and/or vaginitis). Results Vaginitis was diagnosed in three (4.4%) participants, while cervicitis was detected in 16 (23.5%) women. None of the participants reported any high risk sexual behavior. However, 28% of the participants reported having had STI diagnosis in the past and was associated (P<0.008) with abnormal pelvic results. Additionally, women with lower education were associated (p<0.02) with abnormal pelvic results. Conclusions The high occurrence of cervicitis in our exploratory could indicate the high prevalence of STIs. However, while there could potentially be an unknown epidemic of STIs related to the clinical syndromes, point of care testing practice might help to understand the true prevalence of STIs in Nepali women and also reduce the health burden and consequences of over treatment based on the current symptomatic diagnosis. Kathmandu Univ Med J 2013; 11(4): 268-273